Design of Electronic Medical Record Data Quality Indicator Dictionary at National Brain Center Hospital Jakarta - Fatia Fiqri Wahyuni; Hosizah; Sri Jumiati Agustina (Jurnal Rekam Medis dan Informasi Kesehatan, 2025)
To ensure the quality of Electronic Medical Records (EMR), indicators are needed that function as measuring tools and performance evaluations. These indicators are formulated in the form of an indicator dictionary, which describes operational information to measure performance systematically. Currently, the National Brain Center Hospital (RSPON) does not have an EMR indicator dictionary. Therefore, this study aims to design and test an EMR indicator dictionary, especially in outpatient service units. The study used the Research and Development (R&D) method with the RAND/UCLA Appropriateness Method approach, implemented from November 2024 to January 2025. Based on the method above, the research stages include designing an EMR indicator dictionary using data collection methods through interviews with heads of medical record work units, testing the feasibility of the EMR indicator dictionary using the Delphi technique through a questionnaire involving four experts, and testing EMR indicators through document review of 64 EMR samples. Data analysis used content and descriptive analysis. The results show that the designed indicator dictionary contains operational definitions, data sources, data collection methods, and achievement targets of 100% which are made in accordance with applicable standards. Four experts in the Delphi method agreed that the draft RME indicator dictionary was feasible to use. From the results of the review of 64 RMEs, 50 RMEs (78.13%) were declared complete and on time, while the timeliness indicator separately reached 96.88%. In conclusion, the dictionary of completeness and timeliness indicators is feasible to use as an evaluation tool for filling RMEs in RSPON.